Metronomic oral cyclosphosphamide as third-line systemic treatment or beyond in patients with inoperable locoregionally advanced recurrent or metastatic nasopharyngeal carcinoma. Issue 15 (April 2017) - Lee, Victor H.F.; Kwong, Dora L.W.; Lam, Ka-On; Lai, Yu-Ching; Li, Yun; Tong, Chi-Chung; Ho, Patty P.Y.; Chan, Wing-Lok; Wong, Lai-San; Leung, Dennis K.C.; Chan, Sum-Yin; Chan, Fong-Ting; et al.
Abstract : Abstract: There is no standard third-line or further systemic treatment for patients with inoperable locoregionally advanced recurrent or metastatic nasopharyngeal carcinoma (NPC). Metronomic oral cyclophosphamide provides an acceptable and cheap option for these heavily pretreated patients who had limited choices. We conducted a prospective phase II single-arm open-label study of metronomic oral cyclophosphamide. Patients with locoregionally advanced recurrent inoperable (rT3/T4, rN2-N3b) or metastatic (rM1) NPC who had Eastern Cooperative Oncology Group (ECOG) performance status (PS) (0–2) and had progressed after at least 2 lines of palliative systemic chemotherapy were eligible. They received oral cyclophosphamide between 50 and 150 mg once daily until progressive disease or unacceptable toxicity. Objective response rate (ORR), disease control rate (DCR), biochemical response (two consecutive declines of plasma EBV DNA after treatment), progression-free survival (PFS), overall survival (OS), and safety profiles were evaluated. A total of 56 patients were recruited. Thirty-three, 13, 6, 3, and 1 patients received cyclophosphamide as 3rd, 4th, 5th, 6th, and 7th line of therapy respectively. After a median follow-up of 9.95 months (range 1.76–59.51 months), the ORR was 8.9% and the DCR was 57.1%. The median PFS and OS were 4.47 and 9.20 months, respectively. Those with PS 1 had longer median PFS (5.49 months) compared to those with PS 2 (3.75 months, P = .011). Besides, those who had locoregionally recurrent disease had better PFS (8.97 months, 95% CI, 0.53–17.41 months) compared to those who had distant metastases (4.14 months, 95% CI, 2.53–5.75 months, P = .020). Multivariable analysis revealed that PS 1 (vs 2) ( P = .020) and locoregional recurrence (vs metastasis) ( P = .029) were the only significant independent prognostic factors of PFS. Around 16 (28.6%) patients developed grade ≥3 adverse events, including malaise (5.4%), hematological (8.9%), gastrointestinal (3.6%), feverish (3.6%), and hemorrhagic (1.8%) events. The median cost of the whole drug treatment was 51.65 US dollars (USD) (range 4.15–142.75 USD) (1 USD = 7.8 HK dollars [HKD]). Metronomic oral cyclophosphamide is an acceptable third-line or beyond systemic therapy for locoregionally advanced recurrent or metastatic NPC with acceptable toxicity and limited financial burden. Abstract : Supplemental Digital Content is available in the text